(untitled) (Bangladesh Rice Journal, 2015)
Nitrogen (N), the most limiting nutrient in Bangladesh, for rice has been studied most rigorously, but its contribution to rice seed production remained relatively unexplored. An experiment was conducted during season (November-April) in 2009-10 at the Bangladesh Rice Research Institute experimental farm, Gazipur, Bangladesh, to evaluate the effect of N fertilizer on seed yield and its quality. The experiment included BRRI dhan28 and BRRI dhan29 and 0, 50, 100, 150, 200 and 250 kg ha-1 N rates. Seed yield increased significantly in a quadratic fashion with the increase of N rate both in BRRI dhan28 and BRRI dhan29. Application of N fertilizer increased seed yield by about 3-4 t ha-1 compared to control. The highest yield of 5.15 and 6.34 t ha-1 was obtained with 150 kg N ha-1 in BRRI dhan28 and BRRI dhan29 respectively. However, the predicted economic optimum doses of N appeared as 156 and 158 kg ha-1 for BRRI dhan28 and BRRI dhan29 respectively. Nitrogen application to rice seed crop did not impair seed quality in terms of germination, viability, vigour and seed color. The seed N concentration ranged from 0.94 to 1.31% in BRRI dhan28 and 0.85 to 1.07% in BRRI dhan29 among different N rates. The seed phosphorus concentration varied from 0.30 to 0.41% in BRRI dhan28 and 0.28 to 0.36% in BRRI dhan29 among different N rates. The seed K varied from 0.23 to 0.27% and 0.20 to 0.23% in BRRI dhan28 and BRRI dhan29 respectively, among different N rates. The average seed protein of BRRI dhan28 (6.59%) was significantly higher than that of BRRI dhan29 (5.68%). Seed N and protein content slightly increased with the increase of N rate. Nitrogen application did not influence phosphorus and magnesium content in rice seed. However, seed potassium slightly decreased with the N application. Bangladesh Rice j. 2014, 18(1&2): 24-32